Exploration of Mental Health and Well-Being of Healthcare Professionals During the COVID-19 Pandemic - Taurzhan K. Aldabergenova; Anthony Abiodun Eniola; Bibi-Aisha Sh. Orynbayeva; Feruza S. Sarsenbayeva; Nurzhamal S. Askarova; Sidikat Shitu (Global Journal on Quality and Safety in Healthcare, 2024)
Introduction In response to curbing the spread of SARS-CoV-2, healthcare professionals (HCPs) encounter a multitude of mental stresses. The primary intent was to explore the mental health and well-being experienced by HCPs in Ekiti State, Nigeria, amid the COVID-19 pandemic. Methods Data were analyzed using inductive qualitative methodology. The study was undertaken among HCPs in two teaching hospitals in Ekiti State during the SARS-CoV-2 outbreak. Convenience sampling techniques were employed to select participants for this study. A comprehensive interview ranging from 30 to 50 minutes per participant was administered to a sample of 14 HCPs (doctors and nurses) representing various departments within the hospital. The interviews were conducted between March 2020 and May 2020. COVID-19 stressful situations, the physiological consequences of stress, personality, disposition, stress management techniques, and coping mechanisms were evaluated. Results The study outcomes indicate that a significant proportion of HCPs currently face mental well-being. The primary sources of stress identified in this study included heavy workloads and pressure from social media platforms and government agencies. The outbreak crisis significantly influenced on their lives and work, with the fear of catching diseases and their anxiety about spreading infections to their loved ones. Conclusions HCPs require a secure working environment during the current circumstances, along with an enhanced support system to alleviate stressors. This study contributes to a significant proportion of HCPs currently facing stress.